2021
DOI: 10.1080/20008198.2021.2009271
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic life events as risk factors for psychosis and ICD-11 complex PTSD: a gender-specific examination

Abstract: Background Numerous studies found robust associations between psychosis and posttraumatic stress disorder (PTSD), but few have examined the relationships between psychosis and recently formulated ICD-11 Complex PTSD (CPTSD). Further, no known study has examined the effects of different traumatic life events on CPTSD and psychotic-like symptoms in a manner that permits gender-specific effects to be identified. Objective Using a nationally representative sample of 1,020 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Number of experiences of sexual assault, sexual harassment, being stalked, emotional abuse and physical or emotional neglect were all significantly higher in females in another paper (Ho et al, 2021 ). Males reported significantly higher rates of physical assault, life-threatening accident or disaster, life threatened with a weapon, war/combat and causing extreme suffering to someone else (Ho et al, 2021 ). This paper scored 80% in quality assessment.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Number of experiences of sexual assault, sexual harassment, being stalked, emotional abuse and physical or emotional neglect were all significantly higher in females in another paper (Ho et al, 2021 ). Males reported significantly higher rates of physical assault, life-threatening accident or disaster, life threatened with a weapon, war/combat and causing extreme suffering to someone else (Ho et al, 2021 ). This paper scored 80% in quality assessment.…”
Section: Resultsmentioning
confidence: 69%
“…Although Ho et al ( 2021 ) found no gender difference in overall CPTSD diagnostic rates, they reported higher cluster-level scores among females, suggesting a symptom-level difference that did not reach diagnostic threshold. Charak et al ( 2023 ) did not report diagnostic rates by gender but reported similar rates among cisgender and gender diverse participants more broadly.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations